Evaluation of Child-Friendly Schools Program in Islamic Schools using the CIPP Model - Jumari, Jumari; Suwandi, Suwandi (IAIN Samarinda, 2020)
This study aims to evaluate the extent of the implementation of the Child Friendly School program at MTsN 6 Jombang. This evaluation research uses the CIPP evaluation model. This research is an evaluative research with a qualitative approach with a type of case study. The data collection technique is done by interview, observation, and documentation methods. While the data analysis stage was carried out in three stages, namely reduction, presentation, and verification. The results showed that: (1) In the context evaluation, it can be said that the program is in accordance with the needs of the community and there is also a legal basis for the implementation of the program; (2) In the evaluation, the input aspect can be said to be very good, because the implementation of the program is handled very well, namely by the formation of a Child Friendly School Team and also the existence of facilities that support the program; (3) Evaluation of the process aspects related to the program shows that the program is carried out very well, including that almost all existing learning processes must include child-friendly elements in the curriculum. Apart from that cooperation is also carried out to all stakeholders; and (4) Regarding the evaluation of the results, it can be seen from the awards that the school has received, both in the academic and non-academic fields, including those related to the Child Friendly School program, which is winning the highest award or the best national level predicate as a Child Friendly School. The results of this evaluation research are expected to contribute to Islamic education institutions as best practice in implementing the Child Friendly School program.